The influence of external factors on bacteriophages--review - Jończyk, E; Kłak, M; Międzybrodzki, R; Górski, A (Folia microbiologica, 2011)
The ability of bacteriophages to survive under unfavorable conditions is highly diversified. We summarize the influence of different external physical and chemical factors, such as temperature, acidity, and ions, on phage persistence. The relationships between a phage's morphology and its survival abilities suggested by some authors are also discussed. A better understanding of the complex problem of phage sensitivity to external factors may be useful not only for those interested in pharmaceutical and agricultural applications of bacteriophages, but also for others working with phages.
Keywords: životní prostředí; Environment; teplota; Osmotic Pressure; bakteriofágy; koncentrace vodíkových iontů; ionty; Bacteriophages; Temperature; Ions; osmotický tlak; Hydrogen-Ion Concentration